FINRA Issues Regulatory Notice on Customers' and Employees' Right To Choose Securities Arbitration. Issue 8 (September 2016) - Gross, Jill I.
Abstract : Access to arbitration in the securities industry's regulated forum is supposed to be guaranteed to customers with brokerage accounts and to employees of broker‐dealers under Financial Industry Regulatory Authority Inc. Rules 12200 and 13200.